AN ACCOUNTING PARADOX. - Hatfield, Henry R. (The Accounting Review, 1928)
Abstract This article focuses on an accounting paradox. If one purchases at par $2,000,000 bonds bearing 5 per cent interest he will receive $50,000 each half year as interest, and at the maturity of the bonds will be repaid his investment of $2,000,000. In this case the amount collected each six months, by cashing the coupons, is the exact amount of interest earned for that period. No adjustment need be made and the amount of cash received each half year may, with propriety and accuracy, be credited to Interest Revenue. But, if the investor buys $1,000,000 5 per cent bonds at 110 and another block of 1,000,000 5 per cent bonds at 90, the ease is different. To be sure, on the face the situation seems identical with that where $2,000,000 bonds are bought at par. In each case there is an initial outlay of $2,000,000, the same sum is collected each time coupons are cashed the repayment of principal is made at the same date in each case and in exactly the same amount. Investment, collections of coupons, and payment of the face of the bonds are identical in time and amount.